(untitled) (International Journal of Physiology, 2019)
Background VEPs of patients who had unilateral visual problems were retrospectively analyzed. The patients N75-P100 amplitudes and P100 latencies of the affected and normal fellow eye were compared. An alternative way of percentage change in amplitude and latency was also correlated with existing (amplitude ratio and absolute prolongation of latency) ways of analysis. Method 66 subjects (52 males & 14 Females) selected for study who had either affected left or right eye. Further, mean of N75-P100 amplitudes & mean P100 latencies were compared in affected and normal eye. On the basis of percentage reduction in the N75-P100 amplitude and percentage increase in the P100 latency on affected eye subjects were categorized in to those only with reduced amplitude (Group A), only with increased latency (Group B) or with both reduced amplitude & increased latency (Group C). Results Out of 66 patients (mean age 39.50±19.06 yr), 52 were males (78.79%, mean age 38.04±19.22 yr) & 14 were females (21.21%, mean age 44.93±18.11 yr). The patients had nearly equal frequency of affection in right and left eye, with slight preponderance to left eye (LE-n= 38, 57.58%; RE-n= 28, 42.42%). The amplitude reduction (p<0.0001) and latency (p<0.0001) prolongation were significant in affected eye. Group A had maximum number of subjects (n=35; 53.03%) followed by Group C (n=21; 31.82%). We observed a significant inverse correlation (Pearson r =-1.00, p<0.0001) between amplitude ratio & percentage change method and a significant direct correlation (Pearson r = 0.98, p<0.0001) between latency increase and percentage increase of latency. Conclusion Frequency of unilateral involvement in both the eyes is nearly equal. Reduction of N75-P100 amplitude is the most commonly observed abnormal VEP parameter. Percentage Change method can be utilized in future for such studies.